Mutu Fisik dan Daya Terima Body Scrub dengan Variasi Konsentrasi Sari Buah Nanas (Ananas comosus (L.) Merr) - Ambarwati, Rini; Wulandari, Asri; Herlina, Eka (Jurnal Medika Farmaka, 2023)
Introduction: Pineapple fruit contains vitamins such as vitamin C, vitamin A, vitamin B1, and vitamin B6, which are good for the skin and overall health. Body scrub is one of the skin care products that functions to remove dead skin cells and smoothen the skin so that the skin will be healthier. This study aims to find out that pineapple can also be used as an active ingredient in the formulation of body scrub preparations. Methods: In this study, pineapple juice was varied in the formulation of body scrub preparations. The evaluation of body scrub preparations includes viscosity testing, irritation, organoleptic testing with hedonic test method, pH, homogeneity, and emulsion type. Results: The results of the organoleptic testing of body scrub preparations with the hedonic test method showed that the most preferred formula was formula 1 with a pineapple juice concentration of 5%. Body scrub preparations without the addition of pineapple juice are white, while body scrub preparations with the addition of pineapple juice are ivory white and have good homogeneity. The pH and M/A type and viscosity of all formulas were obtained in accordance with the literature. Body scrub preparations do not cause irritation and are safe to use. Conclusion: The formulation of pineapple juice body scrub preparations at a concentration of 5%, 10%, and 15% have good physical quality. Body scrub preparations from pineapple juice have good physical quality and acceptability, namely in the 5% formula where the viscosity value is 5390 cp, no irritation occurs, the hedonic test results show significant differences in all formulas, homogeneous preparations, M/A type emulsion preparations, and have a pH of 6.63.